Mutations of glutamate-84 at the putative potassium-binding site affect camphor binding and oxidation by cytochrome p450cam. - Westlake, A; Harford-Cross, C; Donovan, J; Wong, L (1999)
Cytochrome P450cam (CYP101) from Pseudomonas putida is unusual among P450 enzymes in that it exhibits co-operative binding between the substrate camphor and a potassium ion. This behaviour has been investigated by mutagenesis of Glu84, a surface residue which forms part of the cation-binding site. Substitutions that neutralize or reverse the charge of this side chain are shown to disrupt the co-operativity of potassium and camphor binding by P450cam, and also to influence the catalytic activity. In particular, replacement of Glu84 by positively charged residues such as lysine results in increased high-spin haem fractions and camphor turnover activities in the absence of potassium, along with decreased camphor dissociation constants. However, in the presence of potassium the camphor dissociation constants of these mutants are significantly increased compared with the wild-type, although the camphor turnover activities remain marginally higher. In contrast, substitution by aspartate results in tighter binding of both potassium and camphor, but has little effect on the enzymatic activity. In all cases the reaction remains essentially 100% coupled and gives 5-exo-hydroxycamphor as the only product. These results suggest that an anionic side chain at the 84 position is crucial for the co-operativity of camphor and cation binding, and that the physiological role for potassium binding by cytochrome P450cam is to promote camphor binding even at the expense of turnover rate, thus allowing the organism to utilize low environmental concentrations of this substrate for growth.